(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents information on the causative agent of infectious diseases in fish caused by aquatic fungi belonging to the saprolegniosis family, which are found in cyprinid fish, and explains that the disease causes significant economic damage to fish farms and that treatment in affected farms is ineffective, therefore, it is very important for practice to study its seasonal dynamics for prevention.